Asuhan Keperawatan Pada Ny. S Dengan Gangguan Sistem Persarafan: Stroke Hemoragik (Intracerebral Hemorrhage) Di Ruang Mawar 1 RSUD Dr. Soeselo Kabupaten Tegal - Khilyatun Niswah; Ahmad Zakiudin (STIKES Columbia Asia Medan, 2026)
Intracerebral hemorrhage (ICH) is the most common type of hemorrhhagic stroke and a leading cause of death and disability in Indonesia. The prevalence of stroke in Indonesia reached 0.83% in 2023, with ICH cases at RSUD dr. Soeselo, Tegal Regency recording 203 cases in 2024 and increasing significantly to 304 cases in 2025. This study aims to describe comprehensive nursing care for a patient with Intracerebral Hemorrhage. The method used was descriptive narrative through a nursing process approach. Nursing assessment of Ny. S (73 years old) revealed subjective data including headache, nausea and vomiting, and weakness in the left hand and foot, while objective data showed blood pressure 180/80 mmHg, MAP 113.3 mmHg, muscle strength of left extremities 2/2, and CT scan results showing a hyperdense lesion (volume 17.17 cc) with perifocal edema in the right thalamus and right corona, partially filling the ventricular system. Four nursing diagnoses were established: decreased intracranial adaptive capacity related to cerebral edema, impaired physical mobility related to decreased muscle strength, knowledge deficit related to lack of information exposure, and risk of falls. Nursing interventions included intracranial pressure management, mobilization support, health education, and fall prevention. After three days of nursing implementation, three nursing diagnoses were resolved, while impaired physical mobility was partially resolved, resulting in discharge planning recommendations including ROM exercises, gradual mobilization, and family involvement in patient care.